THE IMPACT OF INDONESIA’S PALM OIL INDUSTRY ON ECONOMIC AND ENVIRONMENTAL PERFORMANCE - Anis Ria Susanti (Fakultas Ekonomi Universitas IBA, 2022)
Indonesia is number one palm oil producer worldwide. Oil palm development is important for Indonesia’s economy. However, it has some issues regarding economic and environmental performance should be considered. This paper examines the relation of economic and environmental sides of oil palm development in Indonesia. It revealed the relation of gross regional domestic product (GRDP), unemployment rate, environmental quality index and oil palm plantation and oil palm production. This study utilises panel data regression analysis using time dimension 2007 to 2017 in Indonesia. This paper uses two independent variables, oil palm plantation and oil palm production. It has three dependent variables as follows: gross regional domestic product (GRDP) per capita, unemployment rate and environmental quality index. Furthermore, it seems that oil palm plantation has insignificant correlation to gross regional domestic product (GRDP) per capita. However, oil palm production has negatively correlated to gross regional domestic product (GRDP) per capita. Additionally, both oil palm plantation and oil palm production have negative relationship with unemployment rate. It means that for every increasing of oil palm plantation and oil palm production will decrease unemployment rate. The results for the relation between oil palm plantation and oil palm production with environmental quality index is quiet similar. There is no significant relation between those variables.